2016
DOI: 10.3390/ijms17030275
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sialyl-Tn in Cancer

Abstract: Activation of an aberrant glycosylation pathway in cancer cells can lead to expression of the onco-foetal sialyl-Tn (sTn) antigen. STn is a truncated O-glycan containing a sialic acid α-2,6 linked to GalNAc α-O-Ser/Thr and is associated with an adverse outcome and poor prognosis in cancer patients. The biosynthesis of the sTn antigen has been linked to the expression of the sialytransferase ST6GalNAc1, and also to mutations in and loss of heterozygosity of the COSMC gene. sTn neo- or over-expression occurs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
154
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 83 publications
1
154
0
2
Order By: Relevance
“…Increased sialylation can increase local negative charges to physically disrupt cell-cell adhesion, and promote detachment from the tumour mass through electrostatic repulsion [87]. Consistent with this, expression of the cancer-associated sTn-antigen reduces cell adhesion in prostate cancer and increases migration and invasion in breast and gastric carcinoma [8893]. Similarly, ectopic expression of the sialytransferase ST6GAL1 in breast cancer cells has been shown to reduce cell adhesion [94].…”
Section: Activating Invasion and Metastasismentioning
confidence: 95%
“…Increased sialylation can increase local negative charges to physically disrupt cell-cell adhesion, and promote detachment from the tumour mass through electrostatic repulsion [87]. Consistent with this, expression of the cancer-associated sTn-antigen reduces cell adhesion in prostate cancer and increases migration and invasion in breast and gastric carcinoma [8893]. Similarly, ectopic expression of the sialytransferase ST6GAL1 in breast cancer cells has been shown to reduce cell adhesion [94].…”
Section: Activating Invasion and Metastasismentioning
confidence: 95%
“…Non-mucin O-glycans include α-attached via O-mannose, α-linked O-fucose, and the β-linked N-acetylglucosamine (O-GlcNAc) [112]. Small or truncated O-glycans are increased in different types of tumors, including gastric, colon, breast, and pancreatic cancer [113, 114], and their production is associated with a poor prognosis and metastasis [115]. …”
Section: Hypoxia Changes Membrane Glycoconjugates In Tumor Cellsmentioning
confidence: 99%
“…This can be further modified by the addition of terminal Gal (galactose), GlcNAc and sialic acid moieties. O-glycan biosynthesis ST6GALNAC1 Sialylation of O-glycans to produce the cancer-associated sTn antigen (Munkley 2016) Associated with poor prognosis in numerous cancer types (Munkley 2016). Promotes tumourigenicity and metastasis in breast and gastric cancer cells (Julien et al 2006, Ozaki et al 2012 ST6GALNAC1 shown to synthesise sTn and reduce cell adhesion in prostate cancer cells (Munkley et al 2015c, Munkley & Elliott 2016b.…”
Section: Figurementioning
confidence: 99%
“…We also identified the sialyltransferase ST6GalNAc1 as being directly regulated by androgens in prostate cancer cells (Munkley et al 2015c. ST6GalNAc1 adds sialic acid to the Tn antigen to produce the cancer-associated onco-foetal sialyl-Tn (sTn) antigen, which is linked to poor prognosis in numerous cancer types (Munkley 2016). STn is a truncated O-glycan containing a sialic acid α-2,6 linked to GalNAc α-O-Ser/Thr and has been shown to promote tumour growth and metastasis in mouse models (Julien et al 2006, Ozaki et al 2012.…”
Section: :3mentioning
confidence: 99%
See 1 more Smart Citation